Rapists’ motives hard to discover - Janasik, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article focuses on issues of motives of sexual offenders i.e. rapists. The source of atypicality of motives described by the author is a stereotype of sexual reasons for crimes under art. 197 of the Polish Criminal Code, which are not confirmed in psychiatric studies. The cognition of rapists’ motives has a positive influence not only on crime detection but also on the proceedings at the stage of judgment passing and carrying out the penalty (resocialization).